Variants production of Lentinula edodes spores, monokaryon mycelium and dikaryon mycelium by -irradiation - Ibrahim Mahmood,; Azhar Mohamad,; Fauzi Daud,; Zaiton Abdul Kadir,; Hing, Jan Nie; Hisham Hamza Hussain,; Wan Safina Wan Abd Razak,; Airianah O.B.,; Shazrul Fazry, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Lentinula edodes or commonly known as shiitake is a cultivated edible mushroom. This mushroom has been used in pharmaceutical, nutraceutical and cosmeceutical industries. However after years of selective inbreeding, the mushroom suffers from a small genetic pool. In this study, we attempt to produce genetic variants of shiitake via γ-irradiation. Shiitake’s spores and mycelium (both monokaryon (MM) and dikaryon (DM)) were subjected to γ-irradiation (137Cs) at series of doses ranging from 0 to 4000 Gy. Dose responses were evaluated based on mycelium growth performance and survivability. The γ-irradiation LD50 for shiitake’s spores, MM, 3rd DM subculture and 9th DM subculture were 795 Gy, 460 Gy, 735 Gy and 1330 Gy, respectively. Interestingly our result shows those higher subcultures DM are more resistant to γ-irradiation. We observed that MMs which were exposed to higher dose of γ-irradiation show lower numbers of clamp connections compared to control indicating that there are genetic compatibility changes between individual hyphal cells within the irradiated shiitake mycelia. This study revealed the potential of γ-irradiation as a tool to create diversity in shiitake genetic pool towards healthy and sustainable mushroom crops in the industries.